Spoken Russian : Book One - Lesnin, I. M.; Petrova, Luba; Linguistic Society of America, Washington, DC.; Spoken Language Services, Inc., Ithaca, NY.; American Council of Learned Societies, New York, NY. ([Washington, D.C.] : Henry Holt and Com., 1945)
This course in spoken Russian is intended for use in introductory conversational classes. Book I in the two-volume series is divided into two major parts, each containing five learning units and one unit devoted to review. Each unit contains sections including (1) basic sentences, (2) word study and review of basic sentences, (3) listening comprehension, and (4) conversation exercises. The lessons, based on cultural experiences commonly shared by Russians, are structured for independent study. A Russian-English and an English-Russian word list, and a key to exercises and tests are included. For the companion document, see FL 004 869. (RL)
Availability: Spoken Language Services; Inc., P. O. Box 783, Ithaca, N. Y. 14850 ($7.00; records, $50.50; tapes, $70.00; cassettes, $60.50).
Microfiche.
Keywords: Conversational Language Courses; Cultural Education; Independent Study; Language Instruction; Language Skills; Modern Languages; Russian; Slavic Languages; Textbooks